2016
DOI: 10.1016/j.tube.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of economic models used to assess the cost-effectiveness of strategies for identifying latent tuberculosis in high-risk groups

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…An approach entailing IGRA testing, though being clearly preferrable over TST, would have been rather unrealistic in our case due to its high cost and logistical challenges [28,29]. Introduction of IGRA, though to a lesser extent than TST, would have also led to diagnosis of a number of LTBI cases, all needing treatment and regular follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…An approach entailing IGRA testing, though being clearly preferrable over TST, would have been rather unrealistic in our case due to its high cost and logistical challenges [28,29]. Introduction of IGRA, though to a lesser extent than TST, would have also led to diagnosis of a number of LTBI cases, all needing treatment and regular follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…The included studies were also afflicted by quality issues pertaining to structural approaches identified by a previous review, such as failure to address structural uncertainty. [ 12 ] In addition, the studies also showed extensive disparities in the structural approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent systematic review described various structure of models used to predict the cost-effectiveness of TB screening strategies and addressed their quality. [ 12 ] Although it highlighted the influence of several parameters, such as tool’s accuracy, it did not analyze the potential influence of different structural approaches on the cost-effectiveness estimates. [ 12 ] As shown by studies in other disease areas, models’ structural approaches disparities, such as different choices of health states (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations notwithstanding, decision-tree models have been widely applied to inform decisionmaking in multiple settings, such as treatment of rheumatoid arthritis [134], diagnosis of latent tuberculosis infection [135], and health interventions for drug and alcohol problems [136]. …”
Section: Decision-tree Modelsmentioning
confidence: 99%